Quality of charcoal produced using micro gasification and how the new cook stove works in rural Kenya. (22nd August 2017) - Njenga, Mary; Mahmoud, Yahia; Mendum, Ruth; Iiyama, Muyiki; Jamnadass, Ramni; de Nowina, Kristina Roing; Sundberg, Cecilia
Abstract: Wood based energy is the main source of cooking and heating fuel in Sub-Saharan Africa. Its use rises as the population increases. Inefficient cook stoves result in fuel wastage and health issues associated with smoke in the kitchen. As users are poor women, they tend not to be consulted on cook stove development, hence the need for participatory development of efficient woodfuel cooking systems. This paper presents the findings of a study carried out in Embu, Kenya to assess energy use efficiency and concentrations of carbon monoxide and fine particulate matter from charcoal produced using gasifier cook stoves, compared to conventional wood charcoal. Charcoal made from Grevillea robusta prunings, Zea mays cob (maize cob) and Cocos nucifera (coconut shells) had calorific values of 26.5 kJ g −1, 28.7 kJ g −1 and 31.7 kJ g −1 respectively, which are comparable to conventional wood charcoal with calorific values of 33.1 kJ g −1 . Cooking with firewood in a gasifier cook stove and use of the resultant charcoal as by-product to cook another meal in a conventional charcoal stove saved 41% of the amount of fuel compared to cooking with firewood in the traditional three stone open fire. Cooking with firewood based on G. robusta prunings in the traditional open fire resulted in a concentration of fine particulate matter of 2600 μ g m −3, which is more than 100 times greater than from cooking with charcoal made from G. robusta prunings in a gasifier. Thirty five percent of households used the gasifier for cooking dinner and lunch, and cooks preferred using it for food that took a short time to prepare. Although the gasifier cook stove is energy and emission efficient there is a need for it to be developed further to better suit local cooking preferences. The energy transition in Africa will have to include cleaner and more sustainable wood based cooking systems.